2015
DOI: 10.1590/1413-81232015208.11492014
|View full text |Cite
|
Sign up to set email alerts
|

A Polissemia da Governança Clínica: uma revisão da literatura

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 17 publications
1
9
0
5
Order By: Relevance
“…In a recent literature review, Gomes et al (2015) found that the majority of work undertaken in the clinical governance space (regardless of the area of study) has mainly been focused at the micro-level, as opposed to the meso-(i.e., organizationwide practice) or macro-level (i.e., sector wide policy). The work of Sanders (2009) would be considered micro-level change as it relates to change in physical restraint only, not all types of restraint.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent literature review, Gomes et al (2015) found that the majority of work undertaken in the clinical governance space (regardless of the area of study) has mainly been focused at the micro-level, as opposed to the meso-(i.e., organizationwide practice) or macro-level (i.e., sector wide policy). The work of Sanders (2009) would be considered micro-level change as it relates to change in physical restraint only, not all types of restraint.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the investigated variables interpreted activities that represent the particular concept of clinical management, taking into account the existing polysemy around this concept 3 . In this way, as specificities of the concept utilized, we can emphasize (i) in the area of healthcare: the orientation of care to the needs of individual and collective health, as much as the identification of biological, psychological, and social dimensions as in the elaboration of care plans in line with the identified needs, as well as the interaction of the different perspectives of those involved; (ii) in the area of health administration: facing problems and taking advantage of opportunities for the production of healthcare with integrality, quality, efficiency, efficacy, effectiveness, and safety, giving emphasis to teamwork and healthcare networks; and (iii) in the area of health education: respect for the diversity of values and previous knowledge of people, the problematization of challenges in health work, and the use of scientific evidence and reflexive spaces to promote the transformation of practices.…”
Section: Discussionmentioning
confidence: 99%
“…From a logic of cost reduction, associated with the standardization of practices and stemming from managed care, as well as a concept originating in clinical governance concerned with broadening the quality of health systems with efficiency and security, aspects of administration and education have been producing tensions and changes in healthcare [1][2][3][4] . In this field, the terminology "clinical management" was introduced to Brazil by Mendes, in the sense of "developing the technologies of administration of health condition, case management, clinical auditing, and waiting lists" 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Desde a sua criação, a Governança Clínica foi incorporada na literatura com diferentes sentidos a ela atribuída, podendo ser sintetizados em sete temas que sintetizam a análise das fontes: gestão, promoção da qualidade, monitoramento ou auditoria clínica, educação, responsabilidade, segurança no cuidado e dimensão sistêmica [3].…”
Section: /2unclassified